Expression Profiling of Lipolytic and Long-Chain Fatty Acid Biosynthesis Genes in Catfish Larvae Fed With Graded Lipid Levels - Mir, Ishfaq Nazir; Srivastava, P. P.; Bhat, Irfan Ahmad; Dar, Jaffer Yousuf; Agarwal, Deepak (Frontiers in Marine Science, 2020)
This study was designed to investigate the effect of dietary lipid levels on the mRNA transcripts of lipid metabolic regulatory genes. Nine combinations of experimental diets containing graded lipid (80, 100 and 120 g/Kg) and protein (450, 500 and 550 g/Kg) levels were fed to the Clarias magur (Indian walking catfish) larvae from 14-35 dph (day post hatching). All the lipolytic genes such as lipoprotein lipase (LPL), pancreatic triacylglycerol lipase (PL) and bile salt-activated lipase (BAL) and genes for long chain poly unsaturated fatty acid (LC-PUFA) biosynthetic enzymes like fatty acyl desaturase-2 (FADS2), fatty acyl desaturase-5 (FADS5) and elongase (ELOV) were expressed in a wide range of tissues. High abundance of mRNA transcript levels of lipolytic genes was detected in intestine and liver, and similarly, desaturases and elongase were predominantly found to express in liver, brain and intestine. Among the diets a significantly high expression of both lipolytic and LC-PUFA biosynthetic genes were observed at 8% dietarylipid level. The expression of all the studied genes was down-regulated at 12% dietary lipid contents. Hence, the present study concludes that the efficient nutrient utilization and the lipid metabolic pathway occur at the optimum dietary lipid level of 8% in C. magur larvae.